Pengembangan Bahan Ajar Ilmu Pengetahuan Alam Berbasis Integrasi-Interkoneksidi Madrasah Tsanawiyah Negeri Jambi Luar Kota - Mega Yurnawati Sari; Rizalman Rizalman; Eva Gusmira (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2019)
The aims of this study was to develop teaching Materials of Natural Science based on integration-interconnection related on Al-Quran in MTsN Jambi Out City with the validity and hight efektivity. This Research is a study R & D with developed specimen by Ahsyar. Employing of this specimen is adapted by according the needs of this study. and according the needs of this study. and according by object and product characteristics to be developed. This developed specimen invoive by 7 steps. Thats are / there are : 1. Needs analysis and student characteristics. 2. Objective formulation. 3. Formulate the material points. 4. Preparation of evaluation instrumens. 5. Preparation of the script / prototype. 6. Perform expert validation. 7. Test and revise. The research instrument of quality questionnaire and perception of the likert created in the form of validation and specialist of integration-interconnection and Natural and Science teacher response is have a very reasonable criteria. Recentage of ideality by specialist obtain the valve with the average of 87,46% and ideality precentage according to the Natural Science is 95%. Students perception to teaching material on range trial of tained by average percentase of 96% learning effectiveness criteria is 75% of 100% amount of students and effectiveness applied of Natural Science learning based on student cognitive abilities.